Maria do Rosário Ferreira, "Pedro de Barcelos e a Escrita da História", Porto, Estratégias Criativas, 2019. (296 p., ISBN: 978-989-8459-62-6) - Silva, Rafaela (Guarecer. Revista Eletrónica de Estudos Medievais, 2020)
.